Modulation of the Activity of Sp Transcription Factors by Mithramycin Analogues as a New Strategy for Treatment of Metastatic Prostate Cancer - Malek, Anastasia (Public Library of Science, 2012)
Deregulated activity of transcription factors (TFs) of the Sp/KLF family, like Sp1, Sp3 and Sp4, and consequent over-expression of Sp-regulated genes occur frequently in human cancers. This provides the rationale for development of inhibitors of Sp TFs as cancer therapeutics. Mithramycin A (MTM-A) is a natural polyketide that binds GC-rich DNA sequences, inhibits activity of Sp TFs and exhibits potent antitumor activity in experimental systems. However, clinical use of MTM-A is limited by the severe toxicity of the compound. Here, we studied two MTM-A analogues, which had been generated by genetically engineering of the MTM-A biosynthetic pathway, and evaluated their activity in human prostate cancer in cell cultures and mouse models. The compounds, named MTM-SDK and MTM-SK, were highly effective in vitro inhibiting proliferation of prostate cancer cells and transcription of Sp-regulated genes by blocking binding of Sp proteins to the gene promoters When administered to mice, both compounds were well tolerated with maximum tolerated doses of MTM-SDK and MTM-SK, respectively, 4- and 32- fold higher than MTM-A. After systemic administration, both compounds were cleared rapidly from the bloodstream but maintained plasma levels well above the active concentrations required in vitro for inhibition of Sp TF activity and cell proliferation. Consistently, MTM-SDK and MTM-SK inhibited transcription of Sp-regulated genes in prostate tumor xenografts and exhibited potent antitumor activity in subcutaneous and metastatic tumor xenograft models with no or minimal toxicity. Taken together, these data indicate that MTM-SDK and MTM-SK possess significantly improved pharmacological and toxicological properties compared to MTM-A and represent promising drugs for treatment of advanced prostate cancer.